Therapeutic drug monitoring guides the management of patients with chronic non-infectious uveitis treated with adalimumab: a retrospective study. Issue 10 (19th April 2021) - Sejournet, Lucas; Kerever, Sebastien; Mathis, Thibaud; Kodjikian, Laurent; Jamilloux, Yvan; Seve, Pascal
Abstract : Aim: To assess the relevance of therapeutic drug monitoring (TDM) of adalimumab (ADA) treatment for the control of intraocular inflammation and treatment adjustment in chronic non-infectious uveitis (CNIU). Methods: Retrospective study of CNIU patients treated with ADA and for whom at least one dosage of serum ADA level and an antibodies against ADA (AAA) serology were performed, between June 2003 and July 2019. Results: A total of 44 ADA-treated patients benefited from a TDM. A total of 48/79 (61%) TDM were performed in responders, 11/79 (14%) in primary non-responders, and 20/79 (25%) in secondary non-responders. Responders had significantly higher ADA levels than non-responders (p=0.0004). AAA were detectable in six patients, they were primary non-responders (n=2), secondary non-responders (n=3) or responders (n=1). In the five non-responders and immunised patients, ADA was switched (to golimumab or methotrexate). Among non-responders, TDM led to an increased frequency of injections 12/31 (38%), increased dose 1/31 (3%) and switch of treatment 10/31 (32%) (one missing data). No modification of biotherapy was performed 7/31 (22%) and only local or oral corticotherapy was adjusted. In 24/31 cases of therapeutic adjustment in non-responders, an improvement was observed in 87% of cases. Among responders for whom the ADA level was above the efficacy threshold, the frequency of injections was decreased for 15/31 (48.4%) cases and no relapse was observed in 12/15 (80%) cases. Conclusion: TDM of ADA treatment proved relevant to provide CNIU patients with a personalised and optimised treatment course (in terms of frequency and type of drug).